IDENTIFIKASI RUANG TERBUKA HIJAU DI KAWASAN PERUMAHAN GRIYA PANIKI INDAH KECAMATAN MAPANGET KOTA MANADO - Cicilia D. Maarebia; Joice M. Supit; Sandra E. Pakasi (Universitas Sam Ratulangi, 2017)
ABSTRACTResearch of Green Open Space Identification is done in Residential of Griya Paniki Indahin the Sub-district Mapanget of Manado City. An important factor in current environmentalproblems is the large number human population. Population growth is a major factor affecting thedevelopment of settlements and the needs of facilities and infrastructure. Green open space isincreasingly into existence and turned into buildings to meets the needs of urban dwellers.This research was conducted to find out the green open space in the Griya Paniki Indah.Standard of Green Open Space requirement is obtained from literature study. Analysis to obtainthe results used in this study is a spatial analysis, that is by using geographic information systemsoftware, that serves to identify the existing Green Open Space. The results obtained that the areaof Green Open Space in Griya Paniki Indah Resident is 29.31 hectares or 16.95% of the total areaaccordance with applicable law. Based on this it is necessary to develop Green Open Space suchas green line/path or like city park and green environment and the return of natural green functionin the form of protected area.Keywords : Green Open Space, Griya Paniki Indah, Geographic Information System